Toluene Monooxygenase-Catalyzed Epoxidation of Alkenes - McClay, Kevin (American Society for Microbiology, 2000)
Several toluene monooxygenase-producing organisms were tested for their ability to oxidize linear alkenes and chloroalkenes three to eight carbons long. Each of the wild-type organisms degraded all of the alkenes that were tested. Epoxides were produced during the oxidation of butene, butadiene, and pentene but not hexene or octadiene. A strain of Escherichia coli expressing the cloned toluene-4-monooxygenase (T4MO) of Pseudomonas mendocina KR1 was able to oxidize butene, butadiene, pentene, and hexene but not octadiene, producing epoxides from all of the substrates that were oxidized. A T4MO-deficient variant of P. mendocina KR1 oxidized alkenes that were five to eight carbons long, but no epoxides were detected, suggesting the presence of multiple alkene-degrading enzymes in this organism. The alkene oxidation rates varied widely (ranging from 0.01 to 0.33 μmol of substrate/min/mg of cell protein) and were specific for each organism-substrate pair. The enantiomeric purity of the epoxide products also varied widely, ranging from 54 to >90% of a single epoxide enantiomer. In the absence of more preferred substrates, such as toluene or alkenes, the epoxides underwent further toluene monooxygenase-catalyzed transformations, forming products that were not identified.